A benzimidazolium-based organic trication: a selective fluorescent sensor for detecting cysteine in water1. Issue 88 (25th September 2015) - Singh, Amanpreet; Singh, Ajnesh; Singh, Narinder; Jang, Doo Ok
<x xml:space="preserve">Abstract</x> A benzimidazolium- and imidazolium-based trication was developed as a selective fluorescence probe for cysteine.